Free underexpanded jets in a quiescent medium: A review. (August 2015) - Franquet, Erwin; Perrier, Vincent; Gibout, Stéphane; Bruel, Pascal
Abstract: When dealing with high-pressure releases, be it needed by some operating conditions or due to an emergency protocol or even to the occurrence of an accident, one has to consider the relevant risks associated to this leakage. Indeed, in addition to the mechanical and blast effects, the dispersion of the released fluid is of primary importance if it is hazardous, as an example for toxic gases or flammable ones (where explosions or fires may be expected). In fact, despite the numerous studies dealing with underexpanded jets, many aspects of their structure are not clearly described, particularly when one seeks for quantitative predictions. By performing an exhaustive overview of the main experimental papers dealing with underexpanded jets, the present paper aims at clarifying the characteristics which are well known, from those where there is clearly a lack of confidence. Indeed, and curiously enough, such a work has never been done and no review is available on such a topic. Two particular regions have drawn most of the attention so far: the nearfield zone, where the shocks/rarefaction pattern that governs the structure of the jet is encountered, and the farfield zone, where the flow is fully developed and often approximated by an equivalent flow. Finally, some clues are given on the numerical methods that may be used if one wants to study such jets numerically, together with an emphasis on the specific thermodynamical difficulties associated to this kind of extreme conditions.